Система підтримки інвестиційної діяльності - Д'яков, Я. Р. (ХНУРЕ, 2022)
Financial culture in the modern, developed and changing world has become another vital element in the system of skills and rules of conduct. Financial literacy allow a person to not depend on circumstances, the others or the system will. An educated person will choose the most attractive paths in life; create a material basis for further society evolution. In this paper thereby a mathematical algorithm is constructed. Based on a financial dataset (e.g. price fluctuations), it gives a recommendation of making certain investment decisions in the short- or long-term period.
Keywords: інвестиційна діяльність; financial culture